Exploring the gut microbiota’s crucial role in acute pancreatitis and the novel therapeutic potential of derived extracellular vesicles - Li, Yijie; Li, Jie; Li, Sen; Zhou, Shumin; Yang, Jiahua; Xu, Ke; Chen, Yafeng (Frontiers in Pharmacology, 2024)
During acute pancreatitis, intestinal permeability increases due to intestinal motility dysfunction, microcirculatory disorders, and ischemia-reperfusion injury, and disturbances in the intestinal flora make bacterial translocation easier, which consequently leads to local or systemic complications such as pancreatic and peripancreatic necrotic infections, acute lung injury, systemic inflammatory response syndrome, and multiple organ dysfunction syndrome. Therefore, adjusting intestinal ecosystem balance may be a promising approach to control local and systemic complications of acute pancreatitis. In this paper, we reviewed the causes and manifestations of intestinal flora disorders during acute pancreatitis and their complications, focused on the reduction of acute pancreatitis and its complications by adjusting the intestinal microbial balance, and innovatively proposed the treatment of acute pancreatitis and its complications by gut microbiota-derived extracellular vesicles.